The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/healthcare11172378
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and Practices towards Vaccinating Their Children against COVID-19: A Cross-Sectional Study among Pakistani Parents

Zain Ul Harmain,
Noorah A. Alkubaisi,
Muhammad Hasnain
et al.

Abstract: There are typically lower COVID-19 vaccination rates among developing versus higher-income countries, which is exacerbated by greater vaccine hesitancy. However, despite the increasing evidence of safety, parents are still reluctant to vaccinate their children against COVID-19. This is a concern in countries experiencing successive waves, such as Pakistan. Consequently, the objective of this study was to gain better understanding and practice regarding parents vaccinating their children against COVID-19 in Pak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…In contrast to our findings, Harmain et al . [ 20 ] found that 84.7% of parents did not consider COVID-19 to be a very serious issue, and 53.9% considered that their children were not at high risk of COVID-19. Significant inclination ( P <0.001) toward their children’s vaccination was seen among those parents possessing higher education, greater knowledge of COVID-19 and its vaccines, with comorbidities, and whose children got infected with the virus during COVID-19 waves.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to our findings, Harmain et al . [ 20 ] found that 84.7% of parents did not consider COVID-19 to be a very serious issue, and 53.9% considered that their children were not at high risk of COVID-19. Significant inclination ( P <0.001) toward their children’s vaccination was seen among those parents possessing higher education, greater knowledge of COVID-19 and its vaccines, with comorbidities, and whose children got infected with the virus during COVID-19 waves.…”
Section: Discussionmentioning
confidence: 99%